Aluminium adjuvants versus placebo or no intervention in vaccine randomised clinical trials: a systematic review with meta-analysis and Trial Sequential Analysis. Issue 6 (23rd June 2022) - Krauss, Sara Russo; Barbateskovic, Marija; Klingenberg, Sarah Louise; Djurisic, Snezana; Petersen, Sesilje Bondo; Kenfelt, Mette; Kong, De Zhao; Jakobsen, Janus C; Gluud, Christian
Abstract : Objectives: To assess the benefits and harms of aluminium adjuvants versus placebo or no intervention in randomised clinical trials in relation to human vaccine development. Design: Systematic review with meta-analysis and trial sequential analysis assessing the certainty of evidence with Grading of Recommendations Assessment, Development and Evaluation (GRADE). Data sources: We searched CENTRAL, MEDLINE, Embase, LILACS, BIOSIS, Science Citation Index Expanded and Conference Proceedings Citation Index-Science until 29 June 2021, and Chinese databases until September 2021. Eligibility criteria: Randomised clinical trials irrespective of type, status and language of publication, with trial participants of any sex, age, ethnicity, diagnosis, comorbidity and country of residence. Data extraction and synthesis: Two independent reviewers extracted data and assessed risk of bias with Cochrane's RoB tool 1. Dichotomous data were analysed as risk ratios (RRs) and continuous data as mean differences. We explored both fixed-effect and random-effects models, with 95% CI. Heterogeneity was quantified with I 2 statistic. We GRADE assessed the certainty of the evidence. Results: We included 102 randomised clinical trials (26 457 participants). Aluminium adjuvants versus placebo or no intervention may have no effect on serious adverse events (RR 1.18, 95% CI 0.97 to 1.43; very low certainty) and on all-cause mortality (RR 1.02, 95% CI 0.74 to 1.41; very low certainty). No trial reported on quality of life. Aluminium adjuvants versus placebo or no intervention may increase adverse events (RR 1.13, 95% CI 1.07 to 1.20; very low certainty). We found no or little evidence of a difference between aluminium adjuvants versus placebo or no intervention when assessing serology with geometric mean titres or concentrations or participants' seroprotection. Conclusions: Based on evidence at very low certainty, we were unable to identify benefits of aluminium adjuvants, which may be associated with adverse events considered non-serious.